1997
DOI: 10.1377/hlthaff.16.4.205
|View full text |Cite
|
Sign up to set email alerts
|

Will Minority Physician Supply Meet U.S. Needs?

Abstract: We project the future racial and ethnic composition of the U.S. physician workforce under different assumptions. Our projections show that reaching racial and ethnic population parity with a managed care-based requirement of 218 physicians per 100,000 population would require the number of first-year residents to roughly double for Hispanic and black physicians, triple for Native American physicians, and be reduced by about two-fifths for white physicians and two-thirds for physicians of Asian or Pacific Islan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…As patients tend to prefer physicians of their own racial or ethnic group, the demand for minority physicians will likely increase in the coming decades. However, as Libby et al (1997) has demonstrated, at the current rates of production, the supply of minority physicians will fall short of future demand. These trends foreshadow a probable decreased likelihood of race concordance for African Americans and Hispanics in the fiture, a reduction of satisfaction among minority patients, and perhaps a decline in quality of care among minorities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As patients tend to prefer physicians of their own racial or ethnic group, the demand for minority physicians will likely increase in the coming decades. However, as Libby et al (1997) has demonstrated, at the current rates of production, the supply of minority physicians will fall short of future demand. These trends foreshadow a probable decreased likelihood of race concordance for African Americans and Hispanics in the fiture, a reduction of satisfaction among minority patients, and perhaps a decline in quality of care among minorities.…”
Section: Discussionmentioning
confidence: 99%
“…To remedy this situation, calls for increases in the numbers of minority healthcare providers were met with the establishment of affirmative action programs which increased the numbers of minority physicians in the workforce (Carlisle et al 1998;Libby et al 1997). Evaluations of the impact of such policies have largely been limited to examinations of trends and patterns in minority physician production (Libby et al 1997) and studies of the practice settings where minority physicians work (Cantor et al 1996).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 We created a "Diversity Ratio" to measure the degree to which a state's physician composition reflects it demographic composition. Underrepresented minority (URM) physicians were defined as African American, Native American, and Latino, which is consistent with prior literature and the current definition of such physicians as stated by the Association of American Medical Colleges.…”
Section: Study Data and Methodsmentioning
confidence: 99%
“…Currently most, if not all, health care professions do not meet these recommendations. [1][2][3][4][5][6][7][8][9] This divide is likely to continue: the US Census Bureau 10 estimates that the US population in 2050 will consist of approximately 50% those identifying themselves as individuals of color, whereas less than 10% of health care providers identify themselves as individuals of color. 11 Athletic trainers provide care to an extremely diverse patient population, but only 12.25% identify themselves as an individual of color.…”
Section: Introductionmentioning
confidence: 99%